Essays in econometrics : collected papers of Clive W.J. Granger - 349909 Granger, C. W. J. (Clive William John), 1934-; Ghysels, Eric, 1956-; Swanson, Norman R. (Norman Rasmus), 1964-; Watson, Mark W. (Cambridge : Cambridge University Press, 2001)
v. 1. Spectral analysis, seasonality, nonlinearity, methodology, and forecasting -- v. 2. Causality, integration and cointegration, and long memory.